"The Physician's Hand": Work Culture and Conflict in American Nursing - McPherson, Kathryn (Labour / Le Travail, 1984)
This article reviews the book, "'The Physician's Hand': Work Culture and Conflict in American Nursing", by Barbara Melosh.